A Brief Depression Screening Tool for Perinatal Clinical Practice: The Performance of the PHQ‐2 Compared with the PHQ‐9. (30th June 2022) - Gigantesco, Antonella; Palumbo, Gabriella; Cena, Loredana; Camoni, Laura; Trainini, Alice; Stefana, Alberto; Mirabella, Fiorino
Abstract : Introduction: There is ongoing interest in using brief screening instruments to identify perinatal depression in clinical practice. One ultra‐brief screening instrument for depression is the Patient Health Questionnaire‐2 (PHQ‐2), but thus far its accuracy in perinatal clinical practice has been barely researched. In the present study, we aimed to assess the screening accuracy of the PHQ‐2 against the Patient Health Questionnaire‐9 (PHQ‐9) in a large sample of perinatal women. Methods: A total of 1155 consecutive women attending 11 health care centers throughout Italy completed the PHQ‐9 (which includes the PHQ‐2) during pregnancy (27‐40 weeks) or postpartum (1‐13 weeks). Sensitivity, specificity, positive predictive value, negative predictive value, likelihood ratio positive, likelihood ratio negative, and overall accuracy were calculated using cut points 3 or greater and 2 or greater. Results: During pregnancy, PHQ‐2 greater than or equal to 3 revealed low sensitivity (38.4%‐44.7%) but high specificity (97.8%‐99.3%). In postpartum, it revealed moderate sensitivity (56.9%‐70.6%), high specificity (95.8%‐99.8%), and fair overall accuracy in pregnancy (70%). The alternative threshold greater than or equal to 2 revealed very high sensitivity (pregnancy: 92.1%‐95.2%; postpartum: 87.1%‐95.2%), moderate specificity (pregnancy: 78.1%‐83.2%; postpartum: 68.8%‐81.1%) and good overall accuracy, both during pregnancy (87%) and postpartum (84%). Discussion: The PHQ‐2 provided acceptable accuracy for screening for depression compared with the PHQ‐9. In perinatal screening practice, a threshold of 2 or greater should be preferred as this ensures high sensitivity, missing only approximately 6% to 8% of cases, and a false‐positive rate (percentage of women classified as affected with depressive symptoms when they are not) of 19% to 25%.